Neonatal supraventricular tachycardia and necrotizing enterocolitis: case report and literature review - Federico Mecarini; Federica Comitini; Flaminia Bardanzellu; Paola Neroni; Vassilios Fanos (BMC, 2020)
Abstract Background Necrotizing enterocolitis (NEC) and supraventricular tachycardia (SVT) are serious emergencies in the neonatal period. Although these conditions are recognized as distinct pathologies, literature reports suggest that recurrent episodes of SVT may predispose patients to NEC via disturbances in mesenteric blood flow and a decrease in tissue perfusion. Case presentation We present a case of a preterm infant affected by recurrent episodes of SVT who developed the initial stage of NEC on the 17th day of life. Moreover, a detailed description of all the cases described in the literature is reported. Materials and methods An integrative review of the updated literature in the Medline database and PubMed and scientific books and articles was conducted. The research from October 2019 to December 2019 was searched for with MeSH and free terms (necrotizing enterocolitis, supraventricular tachycardia) and was linked by Boolean operators. Conclusions SVT can be considered a risk factor for the development of NEC. Therefore, clinicians should have a high level of suspicion for NEC in infants affected by SVT. This article is the first structured literature review analysing the association between SVT and NEC.